please solve this problem
Attachments:
![](https://hi-static.z-dn.net/files/d5f/8da53eca117bffbe142387b37d05965c.jpg)
Answers
Answered by
4
Answer:
(2x-1)(3x-5)(X+1)
Step-by-step explanation:
plzz see the attached pic
Attachments:
![](https://hi-static.z-dn.net/files/dba/1bfbe0839eeffaae5576a9e7d7cfd3b6.jpg)
Anonymous:
heyyy ju
Answered by
0
Answer:
(x+1)(2x-1)(3x-5)
Step-by-step explanation:
6x³-7x²-8x+5
= 6x³+6x²-13x²-13x+5x+5
= 6x²(x+1)-13x(x+1)+5(x+1)
= (x+1)(6x²-13x+5)
= (x+1)(6x²-3x-10x+5)
= (x+1)[3x(2x-1)-5(2x-1)]
= (x+1)(2x-1)(3x-5)
Similar questions